Integration Of The Scientific Method In Chess Teaching - Tirado, Augusto C.s.b.; Pilatti, Luiz Alberto (Զանգակ հրատ.)
The article evaluated the incorporation of the scientific method in educational chess videos on Lichess, identifying the application of fundamental principles such as observation, hypothesis formulation, experimentation, and analysis. The study highlighted the diversity of educational content, addressing various interests and skill levels within the chess community and balancing theory and practice to promote cognitive and strategic development. It analyzed how integrating the scientific method could revolutionize chess learning, improving specific game skills and analytical competencies transferable to other areas. The analysis of educational videos focused on active experimentation and meticulous analysis of games, especially from elite players. The software was used for transcription and data analysis tools to identify effective pedagogical patterns. Applying the scientific method in chess videos promoted significant cognitive development, emphasizing experimentation and critical analysis. The diversity of content reflected a comprehensive and effective educational ecosystem. Future research should explore the deeper integration of the scientific method in chess teaching, evaluate the effectiveness of these approaches, and adapt them to other disciplines. The importance of rigorous and accessible educational methods was emphasized to enhance techniques and strategies in chess, establishing a standard applicable to various fields.
Keywords: Education